The spatial reconfiguration and its socio-environmental implications of Chachapoyas city, department of Amazonas - Comeca Chuquipul, Miguel Ángel (2021)
Chachapoyas is one of the first cities established by the Spanish during the colonial period of Peru, apparently founded as a strategic location to extend territorial control over the Amazon. Its colonial urban structure with a traditional layout has lasted for more than four hundred years without undergoing relevant modifications. However, from the end of the 20th century to the present, the city has endured continuous demographic pressure, currently considered among the five cities with the highest population growth in Peru. This situation is generating a change in the spatial dynamics of the city, with a disordered and informal expansion, in some cases occupying areas exposed to physical dangers, lacking basic infrastructure and services, turning them into vulnerable areas. This research presents how the city is experiencing differentiated processes of spatial reconfiguration and the behaviors it generates through the description and characterization of spaces. In addition, we evidence the implications and identify the factors that explain a situation of socio-environmental vulnerability.